Electromyography of scapular stabilizers in people without scapular dyskinesis during push-ups: a systematic review and meta-analysis - Arghadeh, Ramin; Alizadeh, Mohammad Hossein; Minoonejad, Hooman; Sheikhhoseini, Rahman; Asgari, Mojtaba; Jaitner, Thomas (Frontiers in Physiology, 2023)
Background: Push-up (PU) is widely considered an effective exercise to stabilize the scapula, especially if performed on unstable surfaces. However, available studies cover a wide range of exercise variations and differ according to exercise prescription, muscle selection and study design. Therefore, findings are contradictory, and conclusions for a proper application of the PU are difficult to draw.To synthesize the available literature on the changes in the activity of the periscapular muscles in individuals without scapular dyskinesis while performing different types of PU on unstable surfaces.Search procedure: Four online databases were searched from the earliest publications to August 9, 2023, using predefined keywords. Out of the 2850 potential references identified in the primary search, 92 studies were reviewed in detail, of which 38 met the inclusion criteria and were included. Methodological quality was evaluated using a standardized form based on the Newcastle-Ottawa scale for observational studies. Data combination was performed using CMA (v3), and the random-effects model was used to calculate the standardized mean difference (SMD) with a 95% confidence interval (CI).: The use of unstable surfaces in people without scapular dyskinesis led to increased activity of the upper trapezius during the PU (P = 0.017; I 2 = 84.95%; SMD = 0.425 [95% CI 0.077, 0.773]) and knee PU (P = 0.023; I 2 = 70.23%; SMD = 0.474 [95% CI 0.066, 0.882]) exercises and increased activity of the middle trapezius (MT) (P = 0.003; I 2 = 64.50%; SMD = 0.672 [95% CI 0.225, 1.119]) and serratus anterior (SA) (P = 0.039; I 2 = 4.25%; SMD = 0.216 [95% CI 0.011, 0.420]) muscles during the push-up plus (PUP) exercise.Using an unstable support base during PU does not necessarily increase the activity of all scapular stabilizers. The amount of muscle activity depends on the type of PU other than the type of support base. If an unstable surface is used, PUP exercise appears to be the most effective modality to increase the quality of training, improve performance, and prevent the occurrence of scapular dyskinesis due to the increase in the activity of the MT and SA muscles.